The growths of Ibn Abi Al- Dunya in his book Al- Yaqeen on The Six Books - Alkourd, Ibrahim Ahmed; Al- Nqlah, Ahmed Muhammad (Journal of Islamic Sciences, 2020)
The study dealt with one of the books of the Sunnah of the Prophet، and added its additions، she studied her foundations، followed the conditions of her narrators، and investigated the critics’ sayings to judge them، Then a summary of her judgment was submitted، and the study concluded that Ibn Abi Al- Dunya’s appendices in his book Al- Yaqeen which have been added on the six books are only five hadiths، three of them are weakly based، two are hassan، one of them is raised، and the other is sent، and the third hadiths reported that the sender is correct if the raised is weak.